Reconstruction of three‐dimensional models for complex female pelvic tumors. Issue 3 (22nd February 2022) - Liu, Yingwei; Meng, Shenglan; Wei, Miao; Dai, Fengqin; Xiao, Lin; Mu, Xiaoling; Tang, Junying
Abstract : 3D reconstructed models appear to be a very reliable method for assessing complex female pelvic tumors prior to surgery.